A Theory of Dissimilarity Between Stochastic Discount Factors - Bakshi, Gurdip; Gao, Xiaohui; Panayotov, George (Management Science, 2021)
This paper proposes a measure of dissimilarity between stochastic discount factors (SDFs) in different economies. The SDFs are made comparable using the respective bond prices as the numeraire. The measure is dimensionless, synthesizes features of the risk-neutral moments of excess currency returns, and can be extracted from currency option prices. Linking theory to data, we provide evidence gathered from (i) the cross section of 45 currency option prices, (ii) the time series of currency returns, (iii) estimated SDFs using model-free restrictions, and (iv) structural models in international finance. This paper was accepted by David Simchi-Levi, finance.